Main challenges in the identification and measurement of indirect costs in projects: A multiple case study - Faria, Bruno Cardoso; Do Vale, João Walter Saunders Pacheco; Facin, Ana Lucia Figueiredo [UNESP]; De Carvalho, Marly Monteiro (FapUNIFESP (SciELO), 2020)
Projects have direct and indirect costs; the direct ones are easily identified and quantified, the indirect ones are difficult to control, because they are generated in favor of more than one project, and even if they are not directly related to the activities, they influence their budget. This study aims to present indirect cost identification methods, analyze the estimation models adopted for its measurement, and also analyze ways of appropriating costs in several projects. The method adopted was the analysis of multiple cases in companies of the industrial, commercial and services sectors. It was verified that projects with greater detail of the scope show less difficulty in identifying indirect costs, directly influencing the method of estimation adopted. The estimate for indirect costs is specific to each company, and its complexity is defined by the volume of data available. The appropriation of indirect costs differs between cases, but has similar objectives in its incorporation in the direct hours of the projects. It is worth highlighting the importance of project planning in the identification of indirect costs, in the choice of measurement methods, and also in the forms of costing for the budget.
Principais desafios na identificação e mensuração dos custos indiretos em projetos: um estudo de múltiplos casos
Keywords: Cost Appropriation; Cost management; Indirect costs; Project costing; Project management